Kidney functions and electrolyte disturbance among Iraqi patients with bladder cancer - Noor Ibraheem Ahmed Ibraheem; Rawaa H. Ali; Mohammed B. Ismail (مجلة كلية الطب, 2023)
Background: Bladder cancer is among the most prevalent cancers worldwide, with 549,393 new cases reported in 2018. Approximately 3% of all new cancer diagnoses and 2.1% of all cancer deaths are due to urinary bladder cancer.